Probing the magnetic superexchange couplings between terminal CuII ions in heterotrinuclear bis(oxamidato) type complexes - Abdulmalic, Mohammad A.; Weheabby, Saddam; Meva, Francois E.; Aliabadi, Azar; Kataev, Vladislav; Büchner, Bernd; Schleife, Frederik; Kersting, Berthold; Rüffer, Tobias (Beilstein Journal of Nanotechnology, 2017)
The reaction of one equivalent of [n-Bu4N]2[Ni(opboR2)] with two equivalents of [Cu(pmdta)(X)2] afforded the heterotrinuclear CuIINiIICuII containing bis(oxamidato) type complexes [Cu2Ni(opboR2)(pmdta)2]X2 (R = Me, X = NO3– (1); R = Et, X = ClO4– (2); R = n-Pr, X = NO3– (3); opboR2 = o-phenylenebis(NR-substituted oxamidato); pmdta = N,N,N’,N”,N”-pentamethyldiethylenetriamine). The identities of the heterotrinuclear complexes 1–3 were established by IR spectroscopy, elemental analysis and single-crystal X-ray diffraction studies, which revealed the cationic complex fragments [Cu2Ni(opboR2)(pmdta)2]2+ as not involved in any further intermolecular interactions. As a consequence thereof, the complexes 1–3 possess terminal paramagnetic [Cu(pmdta)]2+ fragments separated by [NiII(opboR2)]2– bridging units representing diamagnetic SNi = 0 states. The magnetic field dependence of the magnetization M(H) of 1–3 at T = 1.8 K has been determined and is shown to be highly reproducible with the Brillouin function for an ideal paramagnetic spin = 1/2 system, verifying experimentally that no magnetic superexchange couplings exists between the terminal paramagnetic [Cu(pmdta)]2+ fragments. Susceptibility measurements versus temperature of 1–3 between 1.8–300 K were performed to reinforce the statement of the absence of magnetic superexchange couplings in these three heterotrinuclear complexes.
Keywords: bis(oxamidato); crystallographic characterization; diamagnetic; heteronuclear complexes; magnetic superexchange coupling; molecular structure